Laminin and Fibronectin Content of Mouse Glomerular and Tubular Basement Membrane - Brees, Douglas K.; Ogle, Roy C.; Williams, Jr, James C. (Kidney & blood pressure research, 1995)
Because the glomerular basement membrane (GBM) is subject to damage in a multitude of renal diseases, a model of basement membrane permeability properties would be useful for learning more about this important barrier. Isolated, perfused tubular basement membrane (TBM) allows measurement of permeability, but it is not known whether TBM is similar enough to GBM for data to be extrapolated from this model to the glomerulus. As a first approach to assessing differences between GBM and TBM, we looked at composition. Renal glomeruli and tubules were isolated from Swiss-Webster mice by sucrose-gradient centrifugation. GBM and TBM were isolated by sonication in 1% deoxycholate and then subjected to a sequential extraction procedure. Analysis of the solubilized basement membranes by electrophoresis revealed a complex mixture of proteins. Immunoblot analysis demonstrated that, among the proteins, laminin and fibronectin were found exclusively in the guanidine and guanidine/dithiotreitol extracts. The total amount of laminin extracted in GBM, 1.8+0.001 µg/mg dry weight (n = 2 groups animals, by inhibitory ELΙSA), was significantly less than in TBM, 3.4+0.1 µg/mg dry weight (n = 2); however, the total amount of fibronectin extracted did not differ between GBM and TBM, 8.2 ± 0.8 and 7.7 ± 1.0 µg/mg dry weight (n = 2) respectively. Examination of deoxycholate supernatants was carried out to see if components of GBM or TBM were solubilized during isolation of basement membranes. Immunoblot analysis revealed loss of some laminin and fibronectin occurred during the detergent isolation of GBM and TBM. We conclude that GBM and TBM are qualitatively similar in that they have the same protein components, but differ significantly in content of laminin and probably other macromolecular components.